(untitled) (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2026)
This study aims to analyze the influence of price and promotion on buying interest on TikTok Shop through custome trust as an intervening variable, with a focus on Generation Z in Semarang City. The study used a quantitative approach with a causal design and involved 410 respondents who were selected through purposive sampling techniques. Data analysis was carried out using the Structural Equation Modeling (SEM) method based on Partial Least Square (PLS) through SmartPLS 4. The results of the study show that prices have a significant effect on customer confidence and buying interest, both directly and indirectly. On the other hand, promotions only have a significant effect directly on buying interest, but do not show a significant influence on customer trust or an indirect influence on buying interest through trust. These findings show that customer trust is more shaped by the perception of price than by promotions. The implications of this study confirm the importance of a price strategy that is aligned with product quality to build trust and increase Gen Z’s buying interest on social commerce platforms such as TikTok Shop.